Developing an islamic micro-enterprise model for the agricultural sector : the case of clove industry in Zanzibar - Moh'd, Issa Salim (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2013)
The contribution of the agricultural sector to the development of Zanzibar Islands is considerable. This very important sector through clove industry was the economic backbone upon which the then government of Zanzibar relied for its foreign exchange and national revenue. However since the Arabs-ruled government was overthrown as a result of the so-called Zanzibar revolution in 1964, agricultural productivity particularly clove production has continually significantly decreased due to many problems and challenges, especially financial ones. A country that was a world leading exporter of the crop i.e. clove has now witnessed a drastic decrease for the last five decades. Several programmes, measures and policies on the other hand, have been adopted by various administrations to find solutions to the dwindling clove production but they have been fruitless. These solutions have mainly focused on alleviating the financial problems the farmers face. Normally financial intermediaries including banks, cooperatives and micro-enterprises would provide micro-financing to the farmers but with high interest rates along with collateral requirements. Thus, this mode of financing has produced no significant result. This study has therefore examined the problems facing the clove industry in Zanzibar with a special emphasis on the private sector participation and proposed a waqf-zakat-muzara'ah- supply chain model (WAMSCM). Under this model the waqf and zakat resources will be used for the human capital development (of) and provision of a piece of land (to) the farmers. There will be a relationship between farmers and financial institutions primarily based on a partnership where profit and loss are shared by both parties. This will enhance the commitment by and cooperation between both parties to ensure the success of the business. Furthermore, the issues of high interest rates and pledging of collateral that constrain the financial ability of the farmers and their agricultural output are integrally solved by this model. In addition to that, the model has the features of investment and risk diversification for both the private institutions and the farmers that will lead to high clove production and employment generation in the economy of the country. This study used a convenience sampling method to collect data from the sample (Pemba Island) whereby 263 questionnaires were collected representing 97.4% of the distributed questionnaires. The findings of this study are relevant to the current situation facing the clove industry in the isles and satisfactory to the extended proposed model of this study i.e. waqf-zakat-muzara'ah –supply chain model (WZMSCM). The study found that, clove industry in Zanzibar is currently facing enormous challenges namely; prices, monopoly, lack of funding, production cost factor, lack of involvement of private sectors, poverty of farmers, and lack of a viable model. Furthermore, the findings of this study are pleasing to tackle the problems facing the clove industry in Zanzibar. As such, the majority of the respondents agreed that this model will remedy the situation and improve the economic productivity of the crop.